Math, asked by srishtee31, 1 year ago

solve Q.45,46,47...plz dosto with steps..with elimination method..u can tally ur answer given in bracket...​

Attachments:

Anonymous: hii
Anonymous: I'm for xxx
Anonymous: please come here

Answers

Answered by rakhithakur
1

Answer:

hiii sristi

here i uploaded your answer

Step-by-step explanation:

25.  

Let mx − ny = m2 + n2  → (1)

        x − y =  2n

Multiply above equation with n, we get

nx − ny = 2n2  → (2)

subtract (2) from (1)

mx − ny = m2 + n2

nx − ny = 2n2  

−     +      −    

---------------------------------

= (m − n)x = m2 − n2

⇒ (m − n)x = (m − n)(m + n)

∴ x = (m + n)

Put x = (m + n) in   x − y =  2n

⇒ (m + n) − y =  2n

⇒ (m + n) − 2n =  y

∴ y = (m − n)

46.

x/a + y/b = 2

ay + xb = 2ab----------( 1 )

ax - by = a² - b²---------( 2 )

from-----( 1 ) &-------( 2 )

multiply ( 1 ) by "a" ( 2 ) by "b"

abx + a²y = 2a²b

abx - b²y = ba² - b³

-------------------------------------------------

y(a² + b²) = 2a²b - ba² + b³

y(a² + b²) = a²b + b³

y(a² + b²) = b(a² + b²)

y = b [ put in -----( 1 )]

we get,

ay + xb = 2ab

a(b) + xb = 2ab

xb = 2ab - ab

x = ab/b

x = a

47.

bx/a + ay/b = a2 + b2 ......... eq1

x + y = 2ab .... eq 2..

frm eq 1.. b2x + a2y / ab = a2 + b2

-> b2x + a2y = a3b + b3a

-> b2x - b3a = a3b - a2y

->b2 ( x - ab ) = a2 ( ab - y )

-> frm eq 2 ... b2 ( x - x/2 + y/2 ) = a2 ( x/2 + y/2 - y )

-> b2 ( x/2 - y/2 ) = a2 ( x/2 - y/2 )

-> b2x - b2y = a2x - a2y

-> x ( b2 - a2 ) = y ( b2 - a2 )

-> x = y ..

put the value of x in eq 2.... 2y = 2ab

hope this will help!

mark it


srishtee31: thnk u so much....
rakhithakur: no problem
aaru4644: hiiii
Answered by lion0
0

mai answer nahi dugi.........

......

....

Similar questions